Advanced Systems-Level Problem Solving, Volume 3 Manual of Dialectical Thought Forms - Laske, Otto. (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This three-volume set introduces the practice of advanced, 'dialectical' systems-level problem solving in both the social and natural sciences. In social science, it opens new vistas regarding organizational, strategy, and work design. In the natural sciences, it provides heretofore missing conceptions of physical systems in peril due to the climate crisis. In addition, the author draws conclusions that are important for advancing generative AI. The monograph presents novel conceptual tools that directly impact the internal structure of a systems analyst's mental processing in real time. While the first volume lays the theoretical groundwork for dialectical systems analysis, the second, focusing on the nature of work, lays bare the structure of complex thinking in terms of the 'thought forms' it requires. In order to facilitate better understanding of the principles taught in the first two volumes, the third volume provides a Manual of Dialectical Thought Forms, which is the only one in existence today.
1. Introduction -- 2. Outline of Dialectic: A framework for its practical use -- 3. DTF Manual Section A -- 4. DTF Manual Section B.
Keywords: Psychology, Industrial; Leadership; Organizational Psychology; Work and Organizational Psychology; Leadership Psychology